Multiple Solutions for a Class of -Laplacian Systems - Fu Yongqiang; Zhang Xia (Journal of Inequalities and Applications, 2009)
We study the multiplicity of solutions for a class of Hamiltonian systems with the -Laplacian. Under suitable assumptions, we obtain a sequence of solutions associated with a sequence of positive energies going toward infinity.